Bruch's membrane opening minimum rim width and retinal nerve fiber layer thickness in a normal white population: a multicenter study - Chauhan, Balwantray; Danthurebandara, Vishva M.; Sharpe, Glen P.; Demirel, Shaban; Girkin, Christopher A.; Mardin, Christian Y.; Scheuerle, Alexander F.; Burgoyne, Claude F. (Ophthalmology, 2015)
Purpose - Conventional optic disc margin-based neuroretinal rim measurements lack a solid anatomic and geometrical basis. An optical coherence tomography (OCT) index, Bruch's membrane opening minimum rim width (BMO-MRW), addresses these deficiencies and has higher diagnostic accuracy for glaucoma. We characterized BMO-MRW and peripapillary retinal nerve fiber layer thickness (RNFLT) in a normal population. - Design - Multicenter cross-sectional study. - Participants - Normal white subjects. - Methods - An approximately equal number of subjects in each decade group (20-90 years of age) was enrolled in 5 centers. Subjects had normal ocular and visual field examination results. We obtained OCT images of the optic nerve head (24 radial scans) and peripapillary retina (1 circular scan). The angle between the fovea and BMO center (FoBMO angle), relative to the horizontal axis of the image frame, was first determined and all scans were acquired and analyzed relative to this eye-specific FoBMO axis. Variation in BMO-MRW and RNFLT was analyzed with respect to age, sector, and BMO shape. - Main Outcome Measures - Age-related decline and between-subject variability in BMO-MRW and RNFLT. - Results - There were 246 eyes of 246 subjects with a median age of 52.9 years (range, 19.8-87.3 years). The median FoBMO angle was −6.7° (range, 2.5° to −17.5°). The BMO was predominantly vertically oval with a median area of 1.74 mm2 (range, 1.05-3.40 mm2). Neither FoBMO angle nor BMO area was associated with age or axial length. Both global mean BMO-MRW and RNFLT declined with age at a rate of −1.34 μm/year and −0.21 μm/year, equivalent to 4.0% and 2.1% loss per decade of life, respectively. Sectorially, the most rapid decrease occurred inferiorly and the least temporally; however, the age association was always stronger with BMO-MRW than with RNFLT. There was a modest relationship between mean global BMO-MRW and RNFLT (r = 0.35), whereas sectorially the relationship ranged from moderate (r = 0.45, inferotemporal) to nonexistent (r = 0.01, temporal). - Conclusions - There was significant age-related loss of BMO-MRW in healthy subjects and notable differences between BMO-MRW and RNFLT in their relationship with age and between each other. Adjusting BMO-MRW and RNFLT for age and sector is important in ensuring optimal diagnostics for glaucoma.
Gesehen am 13.11.2020